Komparasi Penjatuhan Tindakan Rehabilitasi Menurut Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika (Studi Kasus Putusan Nomor 375/Pid.Sus/2015/PN.Jkt.Sel., Putusan Nomor 191/Pid.Sus/2015/PN.Jkt.Sel., dan Putusan Nomor 436/Pid.Sus/2015/PN.Jkt.Sel. - Alia Nabila; Mety Rachmawati (Jurnal Hukum Adigama, 2019)
Narcotics can cause changes in consciousness and cause dependence. Drug use is often needed. Regarding the Narcotics Law Number 35 of 2009 gave birth to an effort to cure the perpetrators of narcotics abuse, namely rehabilitation. Rehabilitation is a recovery effort so that a person can return to his previous state. However, not all cases of drug abuse can be sought for rehabilitation. In the case of perpetrators of narcotics abuse, rehabilitation has been sought as seen in the decision number 191/Pid.Sus/2015/PN.Jkt.Sel., while in the decision number 375/Pid.Sus/2015/PN.Jkt.Sel., and decision number 436/Pid.Sus/2015/PN.Jkt. Cells, narcotics abuse is not sought for rehabilitation and even given criminal sanctions. Act to Law No. 35 of 2009 concerning Narcotics against narcotics abusers if proven to abuse narcotics it is compulsory to undergo rehabilitation in accordance with the provisions of Article 127 Paragraph (1) of the Narcotics Law. And the three decisions in decision number 191/Pid.Sus/2015/PN.Jkt.Sel., Decision number 375/Pid.Sus/2015/PN.Jkt.Sel and decision number 436/Pid.Sus/2015/PN.Jkt.Sel., Was charged as a drug abuser.